DETERMINATION OF TRANSITION PARAMETERS BETWEEN MSK ODESSA AND WGS 84 USING ESRI GEOSINFORMATION TECHNOLOGIES - Колосюк, Анатолий; Константинова, Елена; Стадникова, Наталия; Стадников, Владимир (SWorldJournal, 2021)
The purpose of the article is to apply ESRI’s geographic information technologies in practice to determine the parameters of the transition between local coordinate systems and WGS-84. The paper analyzes the possibilities of using modern ESRI software, d